Variation in cone and seed characteristics in a clonal seed orchard of Anatolian black pine [Pinus nigra Arnold subsp. pallasiana (Lamb.) Holmboe] - Sıvacıoğlu, Ahmet; Ayan, Sezgin (Journal of Environmental Biology, 2010)
Cone and seed characteristics of Anatolian black pine were investigated in a clonal seed orchard for two years, 2002 and 2006. The orchard, originated from Kastamonu-Karadere seed stand was established in 1993 by using 1 year-old grafts in an area of 13 ha, at Hanönü-Günlüburun, northern Turkey and includes 30 clones. The results showed that, significant variation exists among clones for 14 of cone and seed traits for 2006. The clones had cone wet weight in range of 16.92 to 38.51g, whereas this value varied in range of 11.16 to 24.06 g for cone dry weight. Cone length varied from 55.19 to 74.43 mm, while cone width varied in range of 26.66 to 36.57 mm. The range of scale number and fertile scale number varied from 80.02 to 110.64 and 38.03 to 56.20, respectively. Among the clones, the seed and filled seed number were 6.70-24.97 and 5.79-21.12, respectively. The 1000 seed weight varied in range of 20.36 to 29.73 g. The respective values of average seed length and width were 6.29 mm and 3.57 mm, while wing length and width were 19.59 mm and 7.21mm. The average seed efficiency was 13.5%. Coefficients of variation among grafts (CVG ) were mostly bigger than among clones (CVC ), indicating high variation within the population. Year to year correlation coefficients for seed and cone characteristics were varied from moderate (0.58) to strong (0.83). The respective broad sense heritability values of clone mean basis (H2 ) for cone dry weight, cone width, 1000 seed weight were 0.77, 0.83 and 0.76. The seed efficiency had a H2 value of 0.43.
Keywords: Clonal variation, Cone, Seed, Anatolian black pine, Turkey, Heritability